Annual Report of the National Administrative Council of the Independent Labour Party : To be Submitted to the Annual Conference, St. Mungo Halls, Glasgow, March 27th to 30th, 1937. (London : Independent Labour Party, 1937)
1937 SA14-023-004 32 pages 15X/2/209/105